2016
DOI: 10.1007/s40735-016-0058-8
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Stability of Cu–10Al–10Zn, Cu–10Al–10Ni, and Cu–10Ni–10Zn Ternary Alloys in Simulated Physiological Solutions

Abstract: Copper-based alloys are widely used in the consumer electronics industry for components such as connector contacts, shielding gaskets, and terminals. Nickel silver is a general term for alloys that contain copper, nickel, and zinc. Nickel silver first became popular as a base metal for silver-plated cutlery and other silverware, notably electro-plated nickel silver, jewelery and coins. In this article, the electrochemical stability of Cu10Ni-10Zn alloy was compared with that of pure copper and two of copper te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…The tested specimens showed similar polarization and passivity characteristics under all conditions. However, the corrosion current densities (Icorr) and corrosion potentials (Ecorr) of the as-cast and aged alloys shift indicates corrosion protection [43]. It is observed in Table 1 that the corrosion current densities were more intense for the as-cast Cu-10Ni alloy.…”
Section: Corrosion Behaviour and Grain Size Effect Potentiodynamic Po...mentioning
confidence: 95%
See 2 more Smart Citations
“…The tested specimens showed similar polarization and passivity characteristics under all conditions. However, the corrosion current densities (Icorr) and corrosion potentials (Ecorr) of the as-cast and aged alloys shift indicates corrosion protection [43]. It is observed in Table 1 that the corrosion current densities were more intense for the as-cast Cu-10Ni alloy.…”
Section: Corrosion Behaviour and Grain Size Effect Potentiodynamic Po...mentioning
confidence: 95%
“…The grain data distribution was well-fitted by a log-normal function of the statistical scale presented as a solid line. A log-normal function depicts that grain structure is mainly poised of small grains completed by larger grains [41] [43].…”
Section: Grain Size Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…In alkaline Na 2 SO 4 solutions, the corrosion resistance of the Cu-Ni alloys increases with the increase of the nickel content. A critical SO 4 -ions concentration was reported, below which the stability decreases and protective film breakdown takes place [9,[13][14][15]. In this paper, focus has been made on the role of Ni content on the corrosion resistance of the Cu-10Al-xNi ternary alloys with constant Al ratio of 10% in neutral Na 2 SO 4 solutions, aiming at the categorization of these alloys according to their stability in this simulated marine solution and to recommend the use of the alloys in such medium, especially for the industrial production of Na 2 SO 4 .…”
Section: Introductionmentioning
confidence: 99%
“…There is a wide range of materials which exhibit the shape memory effect, but only those alloys are commercially attractive which show a substantial amount of strain recovery and generate significant force due to shape change [4]. The electrochemical corrosion of Cu-Ni alloys has been extensively examined under different experimental conditions using various techniques [5][6][7][8][9]. It was found that the Egyptian Journal of Chemistry http://ejchem.journals.ekb.eg/ ________________________________________________ Egypt.…”
Section: Introductionmentioning
confidence: 99%